KONTROVERSI LANDASAN PENGHAPUSAN PIDANA MATI DALAM RUU KUHP NASIONAL - Ketut Pramana Bayu Anggara; I Ketut Rai Setiabudhi (Kertha Negara : Journal Ilmu Hukum, 2013)
Abolition of the death penalty is the current dilemma experienced by the Indonesiangovernment. On the one hand people consider abolition of the death penalty in Indonesiaare the right steps to prevent crime, but on the other hand consider the abolition of thedeath penalty as a fertilizer for growing crime in Indonesia. This paper is made with a viewto explain what rationale into consideration the abolition of the death penalty in Indonesiaand the Indonesian Penal Code draft. This paper also contains the interrelations abolitionof the death penalty against the theory of punishment in Indonesia.